Gas magnetron deposition of structured TiO₂ nanofilms - Dobrovolskiy, A.M.; Goncharov, A.A.; Kostin, E.G.; Frolova, E.K. (Вопросы атомной науки и техники, 2013)
The paper describes the peculiarities of deposition nano-sized titanium dioxide coatings in the cylindrical inverted gas magnetron. It is shown the influence of the main parameters magnetron sputtering, like as working gas pressure and temperature of substrate, on film grain size, porosity and optical properties of deposited TiO₂ nanofilms. The investigations were carried out with films up to 200 nm of thickness. Представлено дані про особливості одержання наноплівок двоокису титану в циліндричному газовому магнетроні. Показано вплив основних параметрів розряду, таких як тиск плазмоутворюючого газу та температура підкладки на структуру, морфологію та оптичні властивості одержуваних покриттів на прикладі стехіометричних плівок ТiO₂ . Представлены данные об особенностях получения нанопленок диоксида титана в цилиндрическом газовом магнетроне. Показано влияние основных параметров разряда, таких как давление плазмообразующего газа и температура подложки на структуру, морфологию и оптические свойства получаемых покрытий на примере стехиометрического ТiO₂.